2003
DOI: 10.1097/00006123-200301000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Subarachnoid Hemorrhage: Subarachnoid Blood Volume, Mortality Rate, Neuronal Death, Cerebral Blood Flow, and Perfusion Pressure in Three Different Rat Models

Abstract: The prechiasmatic SAH model seems to be the most suitable for study of the sequelae after SAH; it produces a significant decrease in CBF, an acceptable mortality rate, and substantial pathological lesions, with high reproducibility. The CBF reduction is predominantly dependent on the amount of subarachnoid blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
131
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(141 citation statements)
references
References 47 publications
10
131
0
Order By: Relevance
“…In line with earlier studies that employed this endovascular perforation model [3,4,5], we observed high acute mortality (43%) that matches mortality rates of about 40% after clinical aneurysmal SAH [13,14]. Previous studies with this model have primarily focused on the first 24 h after SAH [5].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In line with earlier studies that employed this endovascular perforation model [3,4,5], we observed high acute mortality (43%) that matches mortality rates of about 40% after clinical aneurysmal SAH [13,14]. Previous studies with this model have primarily focused on the first 24 h after SAH [5].…”
Section: Discussionsupporting
confidence: 88%
“…A frequently applied model that closely resembles the clinical pathology, involves perforation of the bifurcation of the internal carotid artery into the middle cerebral artery and anterior cerebral artery with an endovascular filament [3]. The arterial rupture leads to immediate extravasation of intracranial blood and acute elevation of intracranial pressure, resulting in significant reduction in cerebral perfusion within the first minutes [3,4,5,6]. In the following hours, intracranial pressure largely recovers, and perfusion is partially restored [6].…”
Section: Introductionmentioning
confidence: 99%
“…In previous reports we showed that the endovascular perforation of the internal cerebral artery and the injection of blood into the prechiasmatic cistern were suitable means of studying the pathophysiology of SAH. 49,50 To characterize these models further, we used them to induce SAH in the present study.…”
mentioning
confidence: 99%
“…22 After injection of blood into the cisterna magna, neurological function usually remains intact, and the mortality rate is surprisingly lower than that in humans. 26 The filament SAH model better mimics the pathophysiological events after aneurysms rupture an intracranial vessel, with a mortality rate similar to that seen in humans (~ 40-50%). The endovascular perforation of the ICA results in a prompt, very reproducible elevation of ICP and acute vasospasm, 4 which is detectable for up to 72 hours after SAH.…”
Section: Discussionmentioning
confidence: 94%